Cultural Forms and Practices in Northeast India
XII, 233 p. 20 illus., 18 illus. in color.
Keywords: The present book examines cultural diversities of Northeast India. The sixteen essays included in the volume cover various aspects of cultural forms and their practices among the communities of Northeast. The present volume is expected to serve as a bridge between vanishing cultural forms and their commodification, on the one hand, and their cultural ritual origins, evolution and significance in identity formation, on the other. The book analyses continuity of cultural forms, their representations and often their reinventions under globalisation. Further, the book underlines historical forces such as colonialism and religious conversion that have transformed communities and their cultural practices. Yet some of the pre-colonial, ritual-performative traditions hold on. Through insightful analyses, this book offers an informed view of the region’s historical, ethnic and cultural practices. It is expected that the volume will be useful for scholars and students interested in Northeast studies.